The Cabotage Principle on Law Enforcement for Licensing Ship Operations in Indonesian Waters - Ratnawati, Elfrida; Arliman S, Laurensius; Budhianti, Meta Indah; Multi Wijaya, Vience Ratna; Razak, Aida Abdul (Lembaga Contrarius Indonesia, 2023)
This study aims to examine and comprehend the cabotage principle on law enforcement for licensing ship operations in Indonesian Waters. This study is a descriptive analysis of normative legal research.Â Â Secondary data, comprising primary, secondary, and tertiary legal materials, is utilized. Techniques for collecting data involve library research, whereas techniques for analyzing data involve legal interpretation.Â The study results show that Indonesia has regulated the cabotage principle in several regulations. However, supervision in applying this principle has not been optimal due to the increase in transactions between countries due to globalization and overlapping shipping permit issues marked by overlapping authority between the 13 (thirteen) mandated ministries/state institutions by 17 (seventeen) laws as law enforcement officers in marine and coastal areas. The overlap in authority referred to is characterized by the same authority to carry out supervision, pursuit, and investigation in Indonesia's maritime and jurisdictional areas.